2014
DOI: 10.1248/bpb.b13-00109
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety Profile Comparison of Colistin and Tigecycline on the Extensively Drug Resistant <i>Acinetobacter baumannii</i>

Abstract: Colistin and tigecycline are the only therapeutic options for extensively drug resistant Acinetobacter baumannii (XDR-AB), but there is little comparative study. This retrospective observation study evaluated two-colistin and tigecycline-antibiotics profiles like treatment success rate, negative conversion rate, the length of hospital stay, intensive care unit (ICU) stay and antibiotics use, mortality rate during hospital stay and adverse event rate, based on the medical record of XDR-AB positive patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 22 publications
(29 reference statements)
0
24
0
2
Order By: Relevance
“…Among them, outer membrane proteins are responsible for the influx of drugs in gram-negative pathogen Acinetobacter baumannii. Compared with the standard Acinetobacter baumannii strains, tigecycline-resistant strains show the alteration in outer membrane permeability [19,20]. And this is accompanied by significant changes in the expression of outer membrane proteins in Acinetobacter baumannii strains.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, outer membrane proteins are responsible for the influx of drugs in gram-negative pathogen Acinetobacter baumannii. Compared with the standard Acinetobacter baumannii strains, tigecycline-resistant strains show the alteration in outer membrane permeability [19,20]. And this is accompanied by significant changes in the expression of outer membrane proteins in Acinetobacter baumannii strains.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the nephrotoxicity of colistin was not significantly different compared to tobramycin (39), immepenem (32) or ampicillin/sulbactam (42), while the colistin-based treatment had a significantly higher nephrotoxicity than tigecycline-based treatment (36,41).…”
Section: Nephrotoxicitymentioning
confidence: 95%
“…Kwon SH et al reported that in A. baumannii infection, microbiologically negative conversion rate was significantly higher in the colistin group than the tigecyclin group, but there was no statistically significant difference in mortality rate between the two groups during hospital stay (36). While another retrospective study, including 294 adults with MDR A. baumannii pneumonia, found an excess mortality of 16.7% in the tigecycline group (41).…”
Section: Monotherapymentioning
confidence: 99%
See 2 more Smart Citations